Solving Equations by Factoring
The general form of a quadratic equation is: Solving Quadratic Equations The general form of a quadratic equation is: ax2 + bx + c = 0 For example : x2 – 3x + 2 = 0
We’ll use the Zero-Factor Property: Solving Quadratic Equations We’ll use the Zero-Factor Property: For any two numbers a and b, If ab = 0, then a = 0 or b = 0.
Solve: x2 – 3x + 2 = 0 (x – 1)(x – 2) = 0 So, we know that: x – 1 = 0 Example 1: Solve: x2 – 3x + 2 = 0 (x – 1)(x – 2) = 0 So, we know that: x – 1 = 0 or x – 2 = 0 x = 1 or x = 2
Solve 3x2 + 6x = 0 Solution : 3x(x + 2) = 0 3x = 0 or x + 2 = 0 x = 0 Example 2: Solve 3x2 + 6x = 0 Solution : 3x(x + 2) = 0 3x = 0 or x + 2 = 0 x = 0 or x = – 2
Solution : 5x = 6 – 6x2 6x2 + 5x – 6 = 0 (3x – 2)(2x + 3) = 0 Example 3: Solution : 5x = 6 – 6x2 Get rid of fractions! 6x2 + 5x – 6 = 0 (3x – 2)(2x + 3) = 0 3x – 2 = 0 or 2x + 3 = 0 or
Solution : x(6x2 – x – 2) = 0 x(3x – 2)(2x +1) = 0 x = 0 or 3x – 2 = 0 Example 4: Solution : x(6x2 – x – 2) = 0 Factor out GCF!! x(3x – 2)(2x +1) = 0 x = 0 or 3x – 2 = 0 or 2x + 1 = 0 x = 0,
Solving Equations by Factoring: Write the equation with 0 on right-hand side. Factor the left-hand side. Set each factor equal to 0. Solve these simpler equations.